2018
DOI: 10.1016/j.pnpbp.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Altered neuro-inflammatory gene expression in hippocampus in major depressive disorder

Abstract: Major Depressive Disorder (MDD) is a common psychiatric disorder for which available medications are often not effective. The high prevalence of MDD and modest response to existing therapies compels efforts to better understand and treat the disorder. Decreased hippocampal volume with increasing duration of depression suggests altered gene expression or even a decrease in neurogenesis. Tissue punches from the dentate gyrus were collected postmortem from 23 subjects with MDD and 23 psychiatrically-normal contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 87 publications
1
54
0
Order By: Relevance
“…Multiple clinical studies and animal experiments have suggested that hippocampal neuroinflammation is involved in the pathological process of depression. 41,42 Anti-inflammatory therapy can help relieve depression and stress-related mood disorders. 43 As an immune activator and cytokine inducer, LPS can lead to immune activation and inflammatory cytokine release, thereby causing depression-like behaviour in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies and animal experiments have suggested that hippocampal neuroinflammation is involved in the pathological process of depression. 41,42 Anti-inflammatory therapy can help relieve depression and stress-related mood disorders. 43 As an immune activator and cytokine inducer, LPS can lead to immune activation and inflammatory cytokine release, thereby causing depression-like behaviour in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated stressors and risk-taking behaviors in 571 adults who died in a large, urban area during the years 1989–2013. Subjects were recruited from the Cuyahoga County Medical Examiner’s office as part of a larger psychological autopsy study which involved post-mortem tissue collection and structured interviews with next-of-kin and other collateral informants regarding decedents’ psychosocial functioning (Mahajan et al, 2018). Decedents who presented to the Medical Examiner’s office with a history of intravenous drug use were excluded from the study in order to reduce risk of disease transmission to study staff who were collecting tissue samples.…”
Section: Methodsmentioning
confidence: 99%
“…2 The possible causes of depression can be altered neurotransmission, hypothalamic-hypophyseal-adrenal axis abnormalities involved in chronic stress, inflammation, reduced neuroplasticity, 3 reduced levels of neurotrophic factors, and glutamate-mediated toxicity. 4 Any situation which activates cortisol secretion may lead to depression because cortisol has a neurotoxic effect directly and indirectly through its hyperglycemic effect. 5 Amygdala, hippocampus and thalamus are the main brain areas affected by depression and there are disruptions in amount and function of neurotransmitters like acetylcholine, dopamine, norepinephrine, glutamate and gammaaminobutyric acid.…”
Section: Introductionmentioning
confidence: 99%